The humane costs of the 1970s and 1980s famines in North Wollo, Ethiopia. - Tadesse, Mesfin (Cogent Arts & Humanities, 2023)
The purpose of this research paper is to investigate the humane costs of the 1973–74 and 1984–85 famine in North Wollo, Ethiopia. In Wollo, the northern side is always prone to drought and famine and its effect beyond the death tolls is also much highest. As a qualitative approach, descriptive analysis and purposive sampling techniques are used. Data's gathered via interview, focused group discussion and document review showed, in the 20 century the two famines of 1973–74 and 1984–85 were the most difficult periods in which the people paid much sacrifice especially from the later which caused not only much death but also unnatural practices, and devotion towards one's own interest (survival).The period passed as a trying times for families, and people of the region. The family ties and support of one another and the social fabric established through time seen hardly survived.